Technological advances in CO2 conversion electro-biorefinery: A step toward commercialization. (September 2016) - ElMekawy, Ahmed; Hegab, Hanaa M.; Mohanakrishna, Gunda; Elbaz, Ashraf F.; Bulut, Metin; Pant, Deepak
Graphical abstract: Highlights: Novel CO2 conversion processes via bio(electro)chemical processes is presented. Technological advancement in commercial CO2 conversion is discussed. A real-field industrial approach was followed for techno-economic evaluation. Integrated biorefinery route for CO2 conversion indicate technological superiority. Abstract: The global atmospheric warming due to increased emissions of carbon dioxide (CO2 ) has attracted great attention in the last two decades. Although different CO2 capture and storage platforms have been proposed, the utilization of captured CO2 from industrial plants is progressively prevalent strategy due to concerns about the safety of terrestrial and aquatic CO2 storage. Two utilization forms were proposed, direct utilization of CO2 and conversion of CO2 to chemicals and energy products. The latter strategy includes the bioelectrochemical techniques in which electricity can be used as an energy source for the microbial catalytic production of fuels and other organic products from CO2 . This approach is a potential technique in which CO2 emissions are not only reduced, but it also produce more value-added products. This review article highlights the different methodologies for the bioelectrochemical utilization of CO2, with distinctive focus on the potential opportunities for the commercialization of these techniques.